Ta'lim Muta'alim Learning Management: Forming the Character of Creative and Tolerant Students at the Nurul Ali Secang Islamic Boarding School - Rowiyanto Rowiyanto; Laili Syarifah; Dahlia Dahlia (LPPM Universitas PGRI Sumatera Barat, 2024)
Education at Islamic boarding schools has an important role in shaping the character of students so that they become creative and tolerant individuals. One effective learning management model is Ta'lim Muta'alim which not only emphasizes academic aspects, but also pays attention to character development and moral values. This research examines the implementation of Ta'lim Muta'alim learning management at the Nurul Ali Secang Islamic Boarding School and its impact on the formation of the character of students into creative and tolerant individuals. This research is qualitative research and a case study type of research with the research location at the Nurul Ali Secang Islamic Boarding School. Yusuf explained that a qualitative approach can be used if you want to see and express an event and look for a deep meaning or understanding of a problem faced in the form of qualitative data, whether in the form of images, words or events. Such as, courtesy to teachers, friends and parents. For example, it can be seen from the words and words of students, they have started to submit to the teacher, when they meet the teacher they always greet and shake hands, before starting lessons they have to pray first, respect knowledge, behave. polite towards teachers even though there are many teachers, many young people here, and many more.